Ammonia toxicity in Southern King Crab (Lithodes santolla, Molina 1742) larvae - Diodato, Soledad Lorena (2019)
Effects of ammonia on zoea I of the Southern King Crab, Lithodes santolla (Decapoda, Lithodidae) were analyzed through acute (96 h) and chronic (29 days in total) assays (seven total ammonia nitrogen (TAN) concentrations: 9, 15, 25, 41, 67, 110, and 182 mg L−1, plus control). The estimated LC50-96 h was 107.97 mg TAN L−1 (1.93 mg NH3-N L−1), while the safe level of ammonia was 10.79 mg TAN L−1 (0.19 mg NH3-N L−1). Survival was highest in the three lowest ammonia concentrations throughout 96 h (93.3%, 90% and 93.3% in 9, 15 and 25 mg TAN L−1, respectively). In chronic assays, the percentage of survival decreased along with the exposure time and the ammonia concentration. Zoeae´s mean life time tended to increase almost gradually with the increment of ammonia concentration. Mean molting time from zoea I to II was 4.06 days, while it increased from zoea II to III, and zoea III to the post-larval stage (6.00 and 8.39 more days, respectively) with ammonia concentration. The percentage of individuals that have molted in every molt stage tended to decrease while ammonia concentration increased. Therefore, the results obtained in the present study bring new information about ammonia toxicity in early stages of development of crab Lithodes santolla, an important commercial species of the Beagle Channel.